2017
DOI: 10.1007/s40519-017-0432-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific issues in eating disorders: a clinical and psychopathological investigation

Abstract: ED in men is a growing phenomenon. Male ED, compared to female ED, show differences in clinical presentation, symptoms and co-morbidities. Despite the use of clinical and psychometric evaluating tools targeting female patients, sex differences do exist and additional studies are required to investigate male specific issues in ED. Level of Evidence Level V, cross-sectional descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Interestingly, the report of compensatory behaviors represented in our sample is similar to those reported in past studies examining EDs in men, suggesting that men engage in more fasting and excessive exercise than women (Valente et al, 2017). This finding indicates that compensatory behaviors among veteran men meeting criteria for an ED may be similar to those found among civilian men meeting criteria for an ED.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the report of compensatory behaviors represented in our sample is similar to those reported in past studies examining EDs in men, suggesting that men engage in more fasting and excessive exercise than women (Valente et al, 2017). This finding indicates that compensatory behaviors among veteran men meeting criteria for an ED may be similar to those found among civilian men meeting criteria for an ED.…”
Section: Discussionsupporting
confidence: 86%
“…Eating disorders affect females approximately 10 times more often than males (Striegel‐Moore et al, ; Valente et al, ). Our study and the animal model developed in this experiment provide an improved understanding of the mechanisms underlying the sexually dimorphic effect of MS not only at the onset of food restriction but also in terms of the behavioral response.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the markedly different incidence of AN in men and women (a 1:5 ratio; Valente et al, ) and the sexually dimorphic effect observed in the ABA model (Achamrah et al, ; Hancock & Grant, ), we performed our study in rats of both sexes. We expect to confirm previously published data showing that females are more susceptible than males to the effects of a combined MS and ABA protocol.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of self-induced vomiting and laxative–diuretic abuse is more typical in males than in females [22]. The presentation of female AN patients with these symptoms may therefore suggest the need for a thorough clinical history as well as the possibility of employing an addiction intervention strategy, such as SMARPP.…”
Section: Discussionmentioning
confidence: 99%